2020
DOI: 10.1002/stem.3281
|View full text |Cite
|
Sign up to set email alerts
|

CD44+ cells determine fenofibrate-induced microevolution of drug-resistance in prostate cancer cell populations

Abstract: Combinations of metabolic blockers (including fenofibrate) with chemotherapeutic drugs interfere with the drug-resistance of prostate cancer cells. However, their effect on cancer stem cells-dependent microevolution of prostate cancer malignancy remains unaddressed. Here, we hypothesize that the combined docetaxel/fenofibrate treatment prompts the selective expansion of cancer stem cells that affects the microevolution of their progenies. Accordingly, we adapted a combined in vitro/in vivo approach to identify… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 45 publications
1
9
0
Order By: Relevance
“…We did not reveal GJIC involvement in the adaptation of PC-3_DCX20 cells to DCX/MET-induced stress (not shown). Neither did DCX/FF-treatment upregulate Cx43 in these cells (not shown), even though it has previously been shown to trigger an expansion of super-resistant and invasive prostate cancer cell lineages from CD44 + cells [28]. Our data indicate that Cx43 can cooperate with Snail-1 via the (hemi)channel-(in)dependent control of mitochondrial stress [36,47,48] and cell invasiveness [33,[49][50][51].…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…We did not reveal GJIC involvement in the adaptation of PC-3_DCX20 cells to DCX/MET-induced stress (not shown). Neither did DCX/FF-treatment upregulate Cx43 in these cells (not shown), even though it has previously been shown to trigger an expansion of super-resistant and invasive prostate cancer cell lineages from CD44 + cells [28]. Our data indicate that Cx43 can cooperate with Snail-1 via the (hemi)channel-(in)dependent control of mitochondrial stress [36,47,48] and cell invasiveness [33,[49][50][51].…”
Section: Discussionmentioning
confidence: 56%
“…We have previously shown that fenofibrate increases the sensitivity of drug-resistant prostate cancer cell lineages to chemotherapeutics [14]. Concomitantly, we observed an array of self-defense responses of prostate cancer cells that survive the initial chemotherapeutic/metabolic shock [28]. Similarly, metformin was shown to interfere with the acquired drug resistance of prostate cancer cells [17].…”
Section: Introductionmentioning
confidence: 66%
“…A Pubmed search with ‘Prostate Cancer Stem Cells’ as the Keyword would turn up > 3000 references. These reported PCSCs manifest a wide diversity of phenotypes including, among others, ABCG2 + [ 218 ], CD133 + [ 219 , 220 , 236 ], CD133 + α2β1 + [ 219 ], CD44 + [ 219 , 232 , 299 , 311 ], ALDH +/hi [ 224 ], MHC −/lo (and PSA −/lo ) [ 226 ], LP-like [ 227 , 238 ] or basal-like [ 231 ], Trop2 +/hi [ 230 ], TOP2A-[ 243 ], hTERT hi [ 250 ], Bmi1 + Sox2 + [ 260 ], CD24 +/hi [ 261 ], CXCR2 + [ 272 ], Zeb1 + [ 280 ], holoclone-forming cells [ 291 ], and CD117(KIT) + [ 310 ]. Many of these PCSC phenotypes overlap with the PCSCs reported by our lab.…”
Section: Introductionmentioning
confidence: 99%
“…PCSCs, in spite of phenotypic diversity, are commonly endowed with high clonogenic and tumor-initiating/tumor-propagating activities. Importantly, PCSCs have been reported to be intrinsically therapy-resistant, including resistance to castration, chemotherapy, radiotherapy and, likely, immunotherapy [ 2 , 3 , 125 , 131 , 138 , 218 , 226 , 227 , 251 253 , 265 , 278 , 299 , 300 , 310 , 313 , 315 ]. For example, the PSA −/lo PCa cells are resistant to castration, antiandrogens, prooxidants and chemodrugs [ 131 , 144 ] and ABCG2 + PCSCs are resistant to ARSIs due to increased efflux of androgens [ 218 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation